A cultura informacional e a formação do jovem pesquisador brasileiro - Janaina Ferreira Fialho (2009)
This study comprehends the analysis of the formative process of researchers in secondary education, through the practice of scientific research, and had as its main objectives: (1) to identify the development of information literacy on the course of researching practices andcognitive, affective and attitudinal possibilities, in scientific initiation, trying to verify the ISP Model`s sustainability in the academic world; (2) to identify, systematize and analyze the constitution of scientific discourse among students; (3) to examine the impacts of searching and using information in the knowledge construction process among students. The literature used in the theoretical framework aimed to collate progress around the theme of information literacy, in a national and international scope, emphasizing the educational environment and the educational role of school library. Brazilian experiences are underscored, such as the Grupo de Estudos em Biblioteca Escolar (School Library Study Group), the Projeto Mobilizador Biblioteca Escolar (School Library Mobilizing Project), the initiatives of the Fundacoes de Amparo a Pesquisa (Foundations for Fomenting Research), and the parameters set by the Sistema Nacional de Avaliacao da Educacao Basica (National System for Evaluation of Basic Education), the Exame Nacional do Ensino Medio (National Exam of Secondary Education) and the Parametros curriculares Nacionais (National Curricular Parameters). The sample consists of 14 students, winners of the Young Scientist Award, sponsored by the National Council for Scientific and Technological Development, in the secondary school category. Students were approached in the states of Bahia, Ceara, Goias, Minas Gerais, Parana, Piaui, Rio de Janeiro, Rio Grande do Norte, Santa Catarina and Sao Paulo. The instruments used for data collection were semi ]structured interviews, carried out through computers and participant observation in the awarded community in the Orkut social network. Methods of content analysis and semantic analysis of the awarded researches discourses were used as data processing treatment. The results suggest the formation of secondary students towards the scientific discourse, and such formation is marked by the assimilation and constitution of an ethical conduct in the process of searching and using information. Given the cultural and educational diversity of the studied reality, it was possible to identify the consolidation and articulation of different knowledge production strategies among young researchers, with emphasis on the development of critical skills,required in the practice of scientific research. Those strategies were represented in the semantic network identified in the awarded texts; in the scientific discourse marks, noticeable in the systematized repertoire; and in the identification of actions, thoughts and strategies, which guide the research activity of young scientists. The study suggests, in concrete terms, that the school library can be an active body in the development ofinformation literacy in Brazilian schools, and that basic education is the preferred stage for the development of informational skills in the practice of research. It was found that the support and engagement of the school and the concerted action by the supervisor are the key elements in the constitution of the young scientist` s profile. It was also concluded thatthe Premio Jovem Cientista (Young Scientist Award) is an important reference in the lives of young researchers, due to the social recognition that is achieved, the opportunity for career development and the scientific learning.